The Motor Girls - Penrose, Margaret (Salt Lake City, UT : Project Gutenberg, 2004)
"The Motor Girls" by Margaret Penrose is a novel written during the late 19th century that focuses on the adventures of a group of spirited young women as they navigate new experiences with their automobiles. The story centers around Cora Kimball, a determined and capable girl, who receives a beautiful new motor car for her birthday, marking the beginning of her journey into the world of motoring and the social dynamics that come with it. At the start of the novel, we meet Cora and her brother Jack as they discuss her new car, which sparks excitement and light-hearted banter between them. Cora is eager to learn how to drive her new machine despite her mother's insistence that she wait until daylight. As the scene progresses, she is joined by her friends, the Robinson twins, and together they venture to a garage to learn more about her car. The opening sets the stage for a mix of youthful exuberance, humor, and the challenges of early automobile life, hinting at future adventures and the complexities of relationships among the characters. (This is an automatically generated summary.)
Release date is 2004-01-01
Produced by an anonymous Project Gutenberg volunteer
Keywords: Adventure stories; Girls -- Societies and clubs -- Juvenile fiction; Automobiles -- Juvenile fiction